Calling the Shots - Imam Ghayth Nur Kashif (International Institute of Islamic Thought, 2003)
While many Americans are just becoming aware of the United States' extraordinary dominance over the UN, Phyllis Bennis has long been a "prophet," warning of the catastrophic consequences of its disproportionate influence over this international body. A prolific writer, whose published works include Beyond the Storm: A Gulf Crisis Reader and Altered States: A Reader in the New World Order (Interlink: 1999. Edited with Michael Moushabeck), Bennis' signature work, Calling the Shots (Interlink: 1998. Edited with Michael Moushabeck), was initially pubfished by Olive Branch Press in 1996 and revised in 2000. ''The latter edition examines US-UN relations at the close of the 20th century and suggests possible ways forward for the world body," according to its back cover promotional endorsements. The 341-page book has 11 chapters: "The Founders," "The History," "Center Stage: The Role and Power of the UN in Washington's Gulf War," "Who Rules: The Struggle for UN Democracy," "Peacekeeping, Intervention, and a Whole New World Out There," "Washington Keeps Its Own Peace," "Peacekeeping Goes to War: Somalia, Rwanda, Haiti, Bosnia,""UN Sanctions: The Not-Quite Warfare," "To the World's Attention," "The Exception: The Middle East and Palestine," "Democratizing the UN," and "The Laws of Empire and the UN's New Internationalism." This is followed by a 19-page appendix entitled "The United Nations Charter and Principal Organs of the UN." ...